New insights into the accumulation of vitamin B3 in Torreya grandis nuts via ethylene induced key gene expression. (1st March 2022) - Suo, Jinwei; Gao, Yadi; Zhang, Haizhen; Wang, Guifang; Cheng, Hao; Hu, Yuanyuan; Lou, Heqiang; Yu, Weiwu; Dai, Wensheng; Song, Lili; Wu, Jiasheng
Highlights: Vitamin B3 levels vary depending on the cultivar. Vitamin B3 biosynthesis occurs mainly via the aspartate pathway. TgAOX and TgQS are key genes involved in vitamin B3 accumulation between cultivars. Ethylene treatment can promote the biosynthesis of vitamin B3 in Torreya grandis nuts. Abstract: Vitamin B3, derived primarily from plant sources, is an essential nutrient for humans. Torreya grandis is rich in vitamin B3, however, the mechanism underlying the biosynthesis and regulation of vitamin B3 in T. grandis remains unclear. A systematic transcriptomic investigation was thus conducted to identify the gene expression pattern of vitamin B3 biosynthesis in 10 T. grandis cultivars. The findings suggest that biosynthesis occurs mainly via the aspartate pathway. Expression and correlation analyses indicate that aspartate oxidase (AOX) and quinolinate synthase (QS) may play important roles in vitamin B3 accumulation. Furthermore, co-expression network and ethephon treatments indicate that the ethylene response factor (ERF) may be involved in the regulation of vitamin B3 biosynthesis in T. grandis nuts. Our findings not only help to elucidate the biosynthesis of vitamin B3, but also provide valuable resource material for future genomic research and molecular-assisted breeding to develop genotypes with higher vitamin B3 levels.